2016
DOI: 10.1080/17475759.2015.1108216
|View full text |Cite
|
Sign up to set email alerts
|

Testing Measurement Equivalence of Eudaimonic and Hedonic Entertainment Motivations in a Cross-cultural Comparison

Abstract: Within Hofstede's framework of individualistic and collectivistic cultures, this contribution examines measurement equivalence of hedonic and eudaimonic entertainment motivations in two different cultures, namely Germany representing a more individualistic culture (N = 180) and Turkey representing a more collectivistic culture (N = 97). By means of a multi-group confirmatory factor analysis, we could secure configural invariance for both hedonic and eudaimonic entertainment motivations across the German and Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…It can also not be guaranteed that translated surveys have the same meaning (in the respective language). Therefore, it has to be acknowledged as one limitation that translated surveys might not grasp the same meaning for both cultural groups as a function of study language and mother tongue (see, e.g., Odağ et al., 2016).…”
Section: Discussion and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can also not be guaranteed that translated surveys have the same meaning (in the respective language). Therefore, it has to be acknowledged as one limitation that translated surveys might not grasp the same meaning for both cultural groups as a function of study language and mother tongue (see, e.g., Odağ et al., 2016).…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…Notably, participants did not differ regarding their interest in the consumption of hedonic media stimuli. Additionally, Odağ et al. (2016) compared participants from an individualist country (Germany) and a collectivist country (Turkey) regarding their answers on the eudaimonic/hedonic entertainment motivation scale.…”
Section: Values (Meaningful) Media and Cultural Differencesmentioning
confidence: 99%
“…Weinmann et al (2016) found evidence for configurated, metric, and scalar invariance for the ARS in different media formats. With a different questionnaire but the same dimensions, Odağ et al (2016) found cultural differences. However, mean scores of our study were comparable with Eden et al (2018).…”
Section: Discussionmentioning
confidence: 97%
“…At the same time, as is the case with most media and communication theories (Odag˘and Hanke, 2018), most of this literature has been ethnocentric so far, with the majority of studies carried out in the USA and Western Europe (Bartsch and Schneider, 2014;Odag˘et al, 2016). The available literature on media entertainment is focused on 'W.E.I.R.D' populations thus far, i.e., individuals from Western, Educated, Industrialised, Rich, Democratic societies (Heinrich et al, 2010: 61).…”
Section: Introductionmentioning
confidence: 99%